Randomized controlled trial of mindfulness-based stress reduction (MBSR) on posttraumatic growth of Chinese breast cancer survivors. Issue 1 (2nd January 2017) - Zhang, Jia-Yuan; Zhou, Yu-Qiu; Feng, Zi-Wei; Fan, Yi-Nan; Zeng, Guang-Chun; Wei, Li-
Abstract: Breast cancer (BC) patients in China suffered from a variety of psychology stress such as perceived stress and anxiety, posttraumatic growth (PTG) as a positive factor could promote their psychology health and quality of life. This study aimed to investigate the efficacy of mindfulness-based stress reduction (MBSR) on promoting PTG, decreasing perceived stress and anxiety of Chinese BC patients. A randomized controlled trial of 60 BC patients (Stages I–III) was conducted. They were randomly divided to the 8-week MBSR group or usual care (UC) group. PTG inventory, Perceived Stress Scale of Chinese version (CPSS) and State Trait Anxiety Inventory (STAI) evaluated the PTG level, perceived stress and anxiety at three times(before intervention-T1, after intervention-T2 and follow up at 3 months-T3). A repeated-measures analysis of variance model was used to compare each outcome measure of two groups at the three times. There was one patient discontinued the intervention and one lose to follow up in MBSR group, finally 58 BC patients completed the research. There was no difference between two groups before the intervention. The results showed significant improvements in MBSR group comparing with the UC group that PTG level was much higher after the 8-week intervention and the follow up ( F = 34.73, p < .00). At the same time, CPSS ( F = 14.41, p < .00) and STAI ( F = 15.24, p < .00) scores were significant decreased at T2 and T3. The results showed that MBSR promoted the level of PTG and decreased perceived stress and anxiety state of Chinese BC patients, and the results persisted at three months after intervention. The research preliminary proved that MBSR was suitable to Chinese BC patients. MBSR should be recommending to BC survivors in China.